An unusual case of monosomy 18p: minor malformations with speech delay - Bora, Elçin; Giray, Ozlem; Ulgenalp, Ayfer; Ozkan, Hasan; Erçal, Derya (The Turkish Journal of Pediatrics, 2005)
An unusual case of monosomy 18p with molecular cytogenetic characterization of 18;21 whole arm translocation who had mild speech delay and normal motor development is presented. A 3.5-year-old boy with complaints of speech delay, open mouth and drooling saliva was the child of a 33-year-old healthy mother and 35-year-old nonconsangineous father with unremarkable prenatal history. Beside delayed speech, hyperactive movements, flat nasal bridge, prominent ears, micrognathia, hypotonia, and overriding of left 3rd the on 2nd toe were present. Cytogenetic studies revealed de novo 45,XY del (18) t(18;21)-21 karyotype, which was confirmed by fluorescence in situ hybridization (FISH).